Evaluación de cumplimiento de la normativa legal relacionada al régimen de facturación en la empresa Izurieta Sanchez e Hijos - Yanza Deleg, Libia Susana (2015)
experience on the issue and billing control adds. A tax invoice is proof of delivering a product or providing a service, which affects the taxpayer issuer (the seller) and the taxpayer receiver (buyer) (Romero Restrepo, FajardoCarderón, & Velez Romero, 2010). The research method is documentary literature, since the study was made on the basis of journals, scientific articles, etc. since it is scientific cases that have been verified, also based on qualitative methodology in which two techniques of data collection used such as interviews and observation, by which they could obtain information from the company development project. The results show the lack of implementation of legislation, so we recommend using the proposed tool for better control of tax processes in the company; exerting greater control in billing revenues to avoid severe penalties and to continue operating normally.